Effect of Tofu Waste Liquid Organic Fertilizer on the Growth and Production of Pulut Corn (Zea mays Ceratina) Plants - Rahmawati, Hidayatul; Andarula Galushasti; Rr. Liliek Dwi Soelaksini; Christa Dyah Utami (International Integrated Agricultural Journal (IIAJ), 2025)
Corn is one of the food crops in Indonesia that has great potential to be developed, one of which is pulut corn. Pulut corn itself is corn with a high amylase content, but the yield of this corn is in the low category. One way to increase the productivity of pulut corn is the use of liquid organic fertilizer made from tofu waste. The research was carried out on the Jember State Polytechnic land in July-October 2024. Using RBD, which consists of a single treatment, namely the concentration of tofu waste. There are six treatment levels, including control, 26 ml/l, 28 ml/l, 30 ml/l, 32 ml/l, and 34 ml/l. The results of the observation parameters will be tested further with BNJ. From the six levels of treatment given, it was found that treatment with a concentration of 34 ml/l could reduce the stem diameter at 21 DAT, the weight of corn cobs per sample. A concentration of 30 ml/l affects the diameter of the cobs, while a concentration of 32 ml/l affects the weight of the cobs per plot. The parameters of plant height and biomass weight provide significant ups and downs.